Anti-inflammatory and wound healing properties of Malaysia tualang honey - Devasvaran, Kogilavanee; Yong, Yoke Keong (Current Science Association, 2016)
Inflammation is a biological response and a defence mechanism by the body to remove harmful stimuli followed by the healing process. Healing is a process of skin and other soft tissue repair at the site of injury. However, uncontrolled inflammation could lead to serious illnesses such as cancer and cardiovascular diseases, which cause great impact on public health and economy. This necessitates supplementation with anti-inflammatory properties to prevent or remove unnecessary inflammation and damage. For ages, Tualang honey (TH) has been used as a natural remedy for inflammation and wounds. TH also exhibits antioxidant, antibacterial and reproductive properties. This review collates the various studies on anti-inflammatory and wound-healing properties of TH. It also presents findings that indicate that honey may ameliorate ultraviolet-induced inflammation of the skin, chemical-induced inflammation of the eyes and oxidative stress on the eyes. Besides, wound-healing properties have also been highlighted here. These data suggest that TH might be a therapeutic agent in the management of inflammation and wound healing. However, there is a need to study the underlying mechanism of action of TH in vitro and in vivo, to develop a better understanding of its potential benefits.